ANALISIS FITOKIMIA EKSTRAK N-HEKSANA DAN FRAKSI DAUN Marsilea crenata Presl. DENGAN GC-MS - Burhan Ma'arif; Mangestuti Agil; Hening Laswati (Faculty of Pharmacy, Universitas Gadjah Mada, 2016)
Estrogen deficiency causes various health problems in postmenopausal women, including osteoporosis. Phytoestrogen emerged as a potential alternative of estrogen with minimum side effects. Green clover (Marsilea crenata Presl.) is a typical plant in East Java which suspected contains estrogen-like substances. The aim of this research was to report the phytochemical properties of M. crenata using GC-MS as a preliminary study. M. crenata leaves were dried and extracted with n-hexane, then separated using vacuum column chromatography to get four fractions, after that the n-hexane extract and four fractions were identified with GC-MS. The results of GC-MS analysis showed some compounds contained in M. crenata leaves like monoterpenoid, diterpenoid, fatty acid compounds, and other unknown compounds. The results obtained in this research indicated a promising potential of M. crenata as medicinal plants, especially as antiosteoporotic agent.